CORRELATION BETWEEN SERVICE OF HEALTH OFFICERS AND HEALTH FACILITIES WITH THE EFFORTS OF THE COMMUNITY EMPOWERMENT IN KASSI-KASSI HEALTH CENTER - haikal alpin (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2019)
Introduction: The community empowerment is a process to grow the awareness, willingness and capacity of the community in knowing, overcoming, maintaining, protecting, and increasing their prosperities at Kassi-Kassi Health Center, Makassar. Method: The research use a descriptive research using the cross sectional approach. The total of research respondents are 100 people. Result: The analysis results using Spearman test reveals the p value = 0.000, which is smaller than the p value =0.05. This indicates that there is a significant correlation between the service of the health officers and the health facilities, and that the empowerment of the community is very strong and positive in its correlation. This means the better is the service by the health officers and the more complete are the health facilities, the better is the empowerment of the community. Conclusion: There is a correlation between the service of the health officers as well as the health facilities and the empowerment of the community. Therefore, it is suggested that the health officers, particularly the nurses shoud increase the capacity in nursing services to the community in the holistic and comprehensive form in order to improve the service quality, the thought basis, and the development of nursing concept.